Non‐invasive and tracheostomy invasive ventilation in amyotrophic lateral sclerosis: Utilization and survival rates in a cohort study over 12 years in Germany. (16th December 2020) - Spittel, Susanne; Maier, André; Kettemann, Dagmar; Walter, Bertram; Koch, Birgit; Krause, Kerstin; Norden, Jenny; Münch, Christoph; Meyer, Thomas
Abstract: Background and purpose: The aim of this study was to investigate utilization rates, treatment pathways and survival prognosis in patients with amyotrophic lateral sclerosis (ALS) undergoing non‐invasive (NIV) and tracheostomy invasive ventilation (TIV) in a real‐world setting. Methods: A prospective cohort study using a single‐centre register of 2702 ALS patients (2007 to 2019) was conducted. Utilization of NIV/TIV and survival data were analysed in three cohorts: (i) non‐NIV; (ii) NIV (NIV without subsequent TIV); and (iii) TIV (including TIV preceded by NIV). Results: A total of 1720 patients with available data were identified, 72.0% of whom ( n = 1238) did not receive ventilation therapy. NIV was performed in 20.8% of patients ( n = 358). TIV was performed in 9.5% of patients ( n = 164), encompassing both primary TIV (7.2%, n = 124) and TIV with preceding NIV (2.3%, n = 40). TIV was more often utilized without previous NIV (25.7% vs. 8.3% of all ventilated patients), demonstrating that primary TIV was the prevailing pathway for invasive ventilation. The median (range) survival was significantly longer in the NIV cohort (40.8 [37.2–44.3] months) and the TIV cohort (82.1 [68.7–95.6] months) as compared to the non‐NIV cohort (33.6 [31.6–35.7] months). Conclusions: Although NIV represents the standard of care, its utilization rate was low. TIV was mainly started without preceding NIV, suggesting that TIV may not be confined to NIV treatment escalation. However, TIV was pursued in a minority of patients who had previously undergone NIV. The survival benefit observed in the patients with NIV was equal to that reported in a controlled pivotal trial, but the prognosis with TIV is highly variable. The determinants of utilization of NIV/TIV and of survival (bulbar syndrome, availability of ventilation‐related home nursing, cultural factors) warrant further investigation. Abstract : Although non‐invasive ventilation (NIV) is standard of care in amyotrophic lateral sclerosis, in a single‐centre observational study, a low utilization rate was found (21%). Tracheostomy invasive ventilation (TIV) was identified in 9.5% of patients. Surprisingly, TIV was pursued in a minority of patients who had experienced NIV before (24% of NIV cohort). The median survival advantage in patients with NIV was 7 months compared to the non‐ventilated cohort. In patients with TIV the median survival benefit was 48.5 months, although the survival prognosis in this cohort showed a high variability. The determinants for utilization of NIV/TIV and of survival warrant further investigation.